Gold Production: A Survey and Forecast - Kitchin, Joseph (The Review of Economics and Statistics, 1929)
THESE notes supplement artides by the present writer in this REVIEW for August I92I and April I924, and bring up to date tables published in these numbers. Table i gives revised figures for the world's production of gold by regions from the high record of 19I5 to I925. The table covers a period of i i years during which the world has produced ?868,500,ooo of gold, of which ?407,000,000 or 47 per cent was contributed by the Transvaal. It is worth noting that of the ?4o80,000,000 which, according to the records, has been produced since I493, ?2,025,000,000 was contributed by the first quarter of the present century, and ?I,568,ooo,ooo by the nineteenth century. Another fact is significant: in i848-75, according to Edward Suess, 88 per cent of the output was derived from alluvial, while today the percentage has fallen to 8 per cent, and banket practically confined to the Rand yields 50 per cent. In reading Table i and the two which follow, it must be remembered that the Rand white miners' strike of January-March I922 reduced the output of that year by about ?6,ooo,ooo. If the strike had not occurred it is probable that the year of lowest production since I9I5 would have been I92I and not I922. One can, therefore, say that, partly as a result of exhaustion of mines, but also as a result of the increased cost of working resulting from the World War, the yearly production fell from ?96,400,000 to ?68,ooo,ooo, or to 70'2 per cent of I9I5, while it has since increased to ?8oooo,ooo, in I925 or 83 per cent of the high record set in I9I5. In I924 and again in I925, but only by a narrow margin the Transvaal set new high records, and Canada did also. Apart from these two, and probably Russia, the principal gold fields of the world were either stationary or declining, and there is distinct indication that, although the recovery in the world's production has probably not yet spent itself, any further advance will be on a more moderate scale than in recent years. As the Transvaal, especially the Rand, con-